"A Woman Question and a Race Problem": Attending to Intersectionality in Children's Literature. Issue 2 (4th March 2021) - Vickery, Amanda Elizabeth; Rodríguez, Noreen Naseem
Abstract: Historical narratives of Black women often focus solely on racial discrimination without acknowledging the structural and systemic gender-based discrimination they faced. Crenshaw's concept of intersectionality draws upon decades of Black feminist scholarship delineating how Black women experience systemic oppression on account of both their race and gender simultaneously and can serve as an important framework to guide more critical conversations related to the long civil right movement. This article considers how three picturebook biographies about Black women who are often overlooked in early social studies education can powerfully demonstrate the intersectional roles of racism and sexism in their lived experiences.